Reduction of input variability using the natural combination potential of spacious distributed offshore wind farms in the German Baltic Sea and the German Bay - Bendfeld, Jörg; Splett, Michael; Lüttig, Reinhold (Proceedings of the 9th German Wind Energy Conference (DEWEK 2008))

Possibilities of reducing the feed-in fluctuations of offshore wind farms by biogas plants - Bendfeld, Jörg; Tigges, Martin; Splett, Michael; Voss, Jürgen (Proceedings of the 9th German Wind Energy Conference (DEWEK 2008))

Wind energy extension potential in the Münsterland - Bendfeld, Jörg; Linders, Marc; Splett, Michael; Wernekinck, U. (Proceedings of the 9th German Wind Energy Conference (DEWEK 2008))

Two Years Operation of Offshore Metmast Arkona Becken Südost in the Baltic - Bendfeld, Jörg; Ditscherlein, Ralf; Splett, Michael; Voss, Jürgen (Proceedings of the 9th German Wind Energy Conference (DEWEK 2008))

Wave and Current Measurements for Offshore Windfarms - Bendfeld, Jörg; Ditscherlein, Ralf; Splett, Michael; Voss, Jürgen (Proceedings of the 9th German Wind Energy Conference (DEWEK 2008))

Local Strategies for Connecting Stations by Small Robotic Networks - Meyer auf der Heide, Friedhelm; Schneider, Barbara (Biologically-Inspired Collaborative Computing)

Bin Packing oder „Wie bekomme ich die Klamotten in die Kisten?“ - Gehweiler, Joachim; Meyer auf der Heide, Friedhelm (Taschenbuch der Algorithmen)

Planar Visibility Counting - Fischer, Matthias; Hilbig, Matthias; Jähn, Claudius; Meyer auf der Heide, Friedhelm; Ziegler, Martin (arXiv:0810.0052)
For a fixed virtual scene (=collection of simplices) S and given observer position p, how many elements of S are weakly visible (i.e. not fully occluded by others) from p? The present work explores the trade-off between query time and preprocessing space for these quantities in 2D: exactly, in the approximate deterministic, and in the probabilistic sense. We deduce the EXISTENCE of an O(m^2/n^2) space data structure for S that, given p and time O(log n), allows to approximate the ratio of occluded segments up to arbitrary constant absolute error; here m denotes the size of the Visibility Graph--which may be quadratic, but typically is just linear in the size n of the scene S. On the other hand, we present a data structure CONSTRUCTIBLE in O(n*log(n)+m^2*polylog(n)/k) preprocessing time and space with similar approximation properties and query time O(k*polylog n), where k<n is an arbitrary parameter. We describe an implementation of this approach and demonstrate the practical benefit of the parameter k to trade memory for query time in an empirical evaluation on three classes of benchmark scenes.

Proceedings of the twentieth annual symposium on Parallelism in algorithms and architectures - SPAA '08

Multiobjective Optimization of Control Trajectories for the Guidance of a Rail-bound Vehicle - Geisler, M.Sc. Jens; Witting, Dipl.-Math. Katrin; Trächtler, Ansgar; Dellnitz, Michael (IFAC Proceedings Volumes)

Domain Spanning Search for the Identification of Solution Patterns for the Conceptual Design of Self-Optimizing Systems - Klöpper, Benjamin; Podlogar, Herbert; Gausemeier, Jürgen; Witting, Katrin (2008 19th International Conference on Database and Expert Systems Applications)

Hybridizing evolutionary strategies with continuation methods for solving multi-objective problems - Schütze, Oliver; Coello Coello, Carlos A.; Mostaghim, Sanaz; Talbi, El-Ghazali; Dellnitz, Michael (Engineering Optimization)

Convergence of stochastic search algorithms to finite size pareto set approximations - Schütze, Oliver; Laumanns, Marco; Coello Coello, Carlos A.; Dellnitz, Michael; Talbi, El-Ghazali (Journal of Global Optimization)

A new approach for online multiobjective optimization of mechatronic systems - Witting, Katrin; Schulz, Bernd; Dellnitz, Michael; Böcker, Joachim; Fröhleke, Norbert (International Journal on Software Tools for Technology Transfer)

Kartellrechtliche Beurteilung von Kooperationen in der Bank- und Kredit-wirtschaft - Krimphove, Dieter (Finanz Betrieb)

Semiautomatische Klassifizierung von CT-Datensätzen zur kombinierten PET/CT Darstellung - Elsner, A.; Fricke, E.; Fricke, H.; Domik, Gitta; Weise, R.; Burchert, W.

Self-Optimization of the Guidance Module of a Rail-bound Vehicle - Geisler, Jens; Witting, Katrin; Trächtler, Ansgar; Dellnitz, Michael (7th International Heinz Nixdorf Symposium: Self-optimizing Mechatronic Systems: Designing the Future)

Konzeption einer Modellierungssprache zur tool-unterstützten Modellierung, Konfiguration und Bewertung hybrider Leistungsbündel - Becker, Jörg; Beverungen, Daniel; Knackstedt, Ralf; Müller, Oliver (Proceedings of the GI-Tagung Modellierung, Workshop Dienstleistungsmodellierung)

Serviceorientierte Informationssystemarchitekturen zur Integration von Produktion und Dienstleistung am Beispiel des WEEE-Recycling - Knackstedt, Ralf; Müller, Oliver (Wertschöpfungsnetzwerke)

Towards a semantic data quality management-using ontologies to assess master data quality in retailing - Becker, Jörg; Matzner, Martin; Müller, Oliver; Winkelmann, Axel (Americas Conference on Information Systems)

An ontology-based service discovery approach for the provisioning of product-service bundles - Knackstedt, Ralf; Kuropka, Dominik; Müller, Oliver; Polyvyanyy, Artem (European Conference on Information Systems)

Aufbau und experimentelle Bewertung eines Systems zur Langzeitklassiﬁkation von EMG-Signalen - Boschmann, Alexander

Selbstoptimierender Cache-Kontroller - Breitlauch, Daniel

Verteilte Simulation von mobilen Robotern mit EyeSim - Ceylan, Toni; Yalcin, Coni

Comparing Evolvable Hardware to Conventional Classifiers for Electromyographic Prosthetic Hand Control - Glette, Kyrre; Gruber, Thiemo; Kaufmann, Paul; Torresen, Jim; Sick, Bernhard; Platzner, Marco (IEEE Adaptive Hardware and Systems (AHS))

A Comparison of Evolvable Hardware Architectures for Classification Tasks - Glette, Kyrre; Torresen, Jim; Kaufmann, Paul; Platzner, Marco (IEEE Intl. Conf. on Evolvable Systems (ICES))

Parallelisierung und Hardware- / Software - Codesign von Partikelfiltern - Happe, Markus

Evolvable Hardware - Tutorial at Architecture of Computing Systems (ARCS) - Torresen, Jim; Glette, Kyrre; Platzner, Marco; Kaufmann, Paul

Advanced Techniques for the Creation and Propagation of Modules in Cartesian Genetic Programming - Kaufmann, Paul; Platzner, Marco (Genetic and Evolutionary Computation (GECCO))

Implementierung und Bewertung des multikriteriellen Optimierungsverfahrens IBEA für den automatisierten Schaltungsentwurf - Knieper, Tobias

On Robust Evolution of Digital Hardware - Knieper, Tobias; Defo, Bertrand; Kaufmann, Paul; Platzner, Marco (Biologically Inspired Collaborative Computing (BICC))

Eine Monitoring- und Debugging-Infrastruktur für hybride HW/SW-Systeme - Niklas, Jörg

Raytracing on a Custom Instruction Set CPU - Östermann, Marco

Design and Evaluation of MicroBlaze Multi-core Architectures - Westerheide, Nico

A cost-effective error detection and roll-back recovery technique for embedded microprocessor control logic - Ghasemzadeh Mohammadi, Hassan; Tabkhi, Hamed; Miremadi, Seyed Ghassem; Ejlali, Alireza (2008 International Conference on Microelectronics)

Structuring Job Search via Local Grammars - Bsiri, Sandra; Geierhos, Michaela; Ringlstetter, Christoph (Research in Computing Science)
The standard approach of job search engines disregards the structural aspect of job announcements in the Web. Bag-of-words indexing leads to a high amount of noise. In this paper we describe a method that uses local grammars to transform unstructured Web pages into structured forms. Evaluation experiments show high efficiency of information access to the generated documents.

Uncertainty Decoding in Automatic Speech Recognition - Haeb-Umbach, Reinhold (2008 ITG Conference on Voice Communication (SprachKommunikation))
The term uncertainty decoding has been phrased for a class of robustness enhancing algorithms in automatic speech recognition that replace point estimates and plug-in rules by posterior densities and optimal decision rules. While uncertainty can be incorporated in the model domain, in the feature domain, or even in both, we concentrate here on feature domain approaches as they tend to be computationally less demanding. We derive optimal decision rules in the presence of uncertain observations and discuss simplifications which result in computationally efficient realizations. The usefulness of the presented statistical framework is then exemplified for two types of realworld problems: The first is improving the robustness of speech recognition towards incomplete or corrupted feature vectors due to a lossy communication link between the speech capturing front end and the backend recognition engine. And the second is the well-known and extensively studied issue of improving the robustness of the recognizer towards environmental noise.

Error Concealement - Haeb-Umbach, Reinhold; Ion, Valentin (Automatic Speech Recognition on Mobile Devices and over Communication Networks)
In distributed and network speech recognition the actual recognition task is not carried out on the user{\rq}s terminal but rather on a remote server in the network. While there are good reasons for doing so, a disadvantage of this client-server architecture is clearly that the communication medium may introduce errors, which then impairs speech recognition accuracy. Even sophisticated channel coding cannot completely prevent the occurrence of residual bit errors in the case of temporarily adverse channel conditions, and in packet-oriented transmission packets of data may arrive too late for the given real-time constraints and have to be declared lost. The goal of error concealment is to reduce the detrimental effect that such errors may induce on the recipient of the transmitted speech signal by exploiting residual redundancy in the bit stream at the source coder output. In classical speech transmission a human is the recipient, and erroneous data are reconstructed so as to reduce the subjectively annoying effect of corrupted bits or lost packets. Here, however, a statistical classifier is at the receiving end, which can benefit from knowledge about the quality of the reconstruction. In this book chapter we show how the classical Bayesian decision rule needs to be modified to account for uncertain features, and illustrate how the required feature posterior density can be estimated in the case of distributed speech recognition. Some other techniques for error concealment can be related to this approach. Experimental results are given for both a small and a medium vocabulary recognition task and both for a channel exhibiting bit errors and a packet erasure channel.

A Novel Uncertainty Decoding Rule With Applications to Transmission Error Robust Speech Recognition - Ion, Valentin; Haeb-Umbach, Reinhold (IEEE Transactions on Audio, Speech, and Language Processing)
In this paper, we derive an uncertainty decoding rule for automatic speech recognition (ASR), which accounts for both corrupted observations and inter-frame correlation. The conditional independence assumption, prevalent in hidden Markov model-based ASR, is relaxed to obtain a clean speech posterior that is conditioned on the complete observed feature vector sequence. This is a more informative posterior than one conditioned only on the current observation. The novel decoding is used to obtain a transmission-error robust remote ASR system, where the speech capturing unit is connected to the decoder via an error-prone communication network. We show how the clean speech posterior can be computed for communication links being characterized by either bit errors or packet loss. Recognition results are presented for both distributed and network speech recognition, where in the latter case common voice-over-IP codecs are employed.
Keywords: automatic speech recognition; bit errors; codecs; communication links; corrupted observations; decoding; distributed speech recognition; error-prone communication network; feature vector sequence; hidden Markov model-based ASR; hidden Markov models; inter-frame correlation; Internet telephony; network speech recognition; packet loss; speech posterior; speech recognition; transmission error robust speech recognition; uncertainty decoding; voice-over-IP codecs

Investigations into Uncertainty Decoding Employing a Discrete Feature Space for Noise Robust Automatic Speech Recognition - Ion, Valentin; Haeb-Umbach, Reinhold (2008 ITG Conference on Voice Communication (SprachKommunikation))
This paper addresses the robustness of automatic speech recognition to environmental noise. In order to account for reliability of the clean feature estimate we employ the feature posterior density conditioned on observed noisy features to perform uncertainty decoding. We investigate two approaches to estimate the posterior using a discrete feature space, first conditioning only on the current observation, and second on the whole feature sequence of an utterance. Experiments with Aurora 2 showed that the latter provides slightly better performance, as it allows for exploiting the temporal correlations between consecutive features.

Blinde Akustische Strahlformung fuer Anwendungen im KFZ - Krueger, Alexander; Warsitz, Ernst; Haeb-Umbach, Reinhold (34. Deutsche Jahrestagung fuer Akustik (DAGA 2008))
In diesem Beitrag werden zwei neuartige akustische Strahlformungsalgorithmen fuer einen Einsatz im KFZ diskutiert. In beiden Verfahren ist fuer jede Frequenzkomponente der Eigenvektor zum groessten Eigenwert eines verallgemeinerten Eigenwertproblems zu bestimmen: bei der einen Varianate stellen die Filterkoeffizienten gerade obigen Eigenvektor dar. Sprachverzerrungen werden mit einem einkanaligen Nachfilter kompensiert. In der anderen Variante, welche die Struktur eines ''Generalized Sidelobe Cancellers'' (GSC) hat, basiert die Blockiermatrix auf obiger Eigenvektorzerlegung.

Blind Speech Separation in Presence of Correlated Noise with Generalized Eigenvector Beamforming - Tran Vu, Dang Hai; Haeb-Umbach, Reinhold (2008 ITG Conference on Voice Communication (SprachKommunikation))
This paper considers the convolutive blind source separation of speech sources in the presence of spatially correlated noise. We introduce a method for estimating the scaled mixing matrix from the sources to the microphones even if coherent noise is present. This is achieved by combining time-frequency sparseness with the generalized eigenvalue decomposition of the power spectral density matrix (PSD) of the noisy speech and noise-only microphone signals. Separation is performed by spatial filtering with coefficients constructed by Gram-Schmidt orthogonalization which places spatial nulls at the interferer{^A}?`s direction. Experimental results show that our approach is capable of separating 2 sources in a reverberant environment (RT60=0ms..500ms) degraded by significant directional noise.

Generalized Eigenvector Blind Speech Separation Under Coherent Noise In A GSC Configuration - Tran Vu, Dang Hai; Krueger, Alexander; Haeb-Umbach, Reinhold (International Workshop on Acoustic Echo and Noise Control (IWAENC 2008))
This Paper deals with a new Technique for multi-channel separation of speech signals from convolutive mixtures under coherent noise. We demonstrate how the scaled transfer functions from the sources to the microphones can be estimated even in the presence of stationary coherent noise. The key to this are generalized eigenvalue decompositions of the power spectral density (PSD) matrices of the noisy speech and noise-only microphone signals with a controlled estimation of these matrices exploiting time-frequency sparseness of the speech sources. Separation is further improved by subsequent Gram-Schmidt orthogonalization which places spatial nulls at the interferers{\rq} directions, while noise reduction is improved by employing a novel blocking matrix and adaptive interference canceller in a Generalized Sidelobe Canceller (GSC)-like structure. We report promising experimental results for 2 speech sources with significant coherent noise in reverberant environments (RT60=0oms..500ms).

Speech enhancement with a new generalized eigenvector blocking matrix for application in a generalized sidelobe canceller - Warsitz, Ernst; Krueger, Alexander; Haeb-Umbach, Reinhold (IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP 2008))
The generalized sidelobe canceller by Griffith and Jim is a robust beamforming method to enhance a desired (speech) signal in the presence of stationary noise. Its performance depends to a high degree on the construction of the blocking matrix which produces noise reference signals for the subsequent adaptive interference canceller. Especially in reverberated environments the beamformer may suffer from signal leakage and reduced noise suppression. In this paper a new blocking matrix is proposed. It is based on a generalized eigenvalue problem whose solution provides an indirect estimation of the transfer functions from the source to the sensors. The quality of the new generalized eigenvector blocking matrix is studied in simulated rooms with different reverberation times and is compared to alternatives proposed in the literature.
Keywords: adaptive interference canceller; adaptive signal processing; array signal processing; beamforming method; eigenvalues and eigenfunctions; generalized eigenvector blocking matrix; generalized sidelobe canceller; interference suppression; matrix algebra; noise suppression; speech enhancement; transfer function estimation; transfer functions

Modeling the dynamics of speech and noise for speech feature enhancement in ASR - Windmann, Stefan; Haeb-Umbach, Reinhold (IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP 2008))
In this paper a switching linear dynamical model (SLDM) approach for speech feature enhancement is improved by employing more accurate models for the dynamics of speech and noise. The model of the clean speech feature trajectory is improved by augmenting the state vector to capture information derived from the delta features. Further a hidden noise state variable is introduced to obtain a more elaborated model for the noise dynamics. Approximate Bayesian inference in the SLDM is carried out by a bank of extended Kalman filters, whose outputs are combined according to the a posteriori probability of the individual state models. Experimental results on the AURORA2 database show improved recognition accuracy.
Keywords: a posteriori probability; AURORA2 database; Bayesian inference; Bayes methods; channel bank filters; extended Kalman filter banks; hidden noise state variable; Kalman filters; noise dynamics; speech enhancement; speech feature enhancement; speech feature trajectory; switching linear dynamical model approach

A novel approach to noise estimation in model-based speech feature enhancement - Windmann, Stefan; Haeb-Umbach, Reinhold (2008 ITG Conference on Voice Communication (SprachKommunikation))
In this paper, the noise estimation for model-based speech feature enhancement in automatic speech recognition (ASR) is investigated. Beside a stationary noise prior, three linear state space models for the (cepstral) noise process are considered. We have derived novel EM algorithms for the estimation of the noise model parameters: A blockwise EM algorithm is applied on noise-only input data. It is supposed to be used during the offline training mode of the recognizer. Further a sequential online EM algorithm is employed to adapt the observation variance in recognition mode which works as well under the asumption of a stationary noise prior and a linear state model for the noise. Experiments on the AURORA4 database lead to improved recognition results with the new state model compared to the assumption of stationary noise.

A segmental HMM based on a modified emission probability - Windmann, Stefan; Haeb-Umbach, Reinhold; Leutnant, Volker (2008 ITG Conference on Voice Communication (SprachKommunikation))
In this paper, a novel segmental Hidden Markov Model (HMM) is proposed. The model is based on a modified emission density where additional statistical dependencies between subsequent frames of the speech signal are considered. In the following we derive an effective search strategy for the modified statistical model. Further an approach to parameter reduction is introduced. Experiments were carried out on the AURORA2 database where consistent im

Virtual Cord Protocol (VCP): A flexible DHT-like routing service for sensor networks - Awad, Abdalkarim; Sommer, Christoph; German, Reinhard; Dressler, Falko (2008 5th IEEE International Conference on Mobile Ad Hoc and Sensor Systems)

Requirements and objectives for secure Traffic Information Systems - Dressler, Falko; Sommer, Christoph; Gansen, Tobias; Wischhof, Lars (2008 5th IEEE International Conference on Mobile Ad Hoc and Sensor Systems)

Realistic Simulation of Network Protocols in VANET Scenarios - Sommer, Christoph; Dietrich, Isabel; Dressler, Falko (2007 Mobile Networking for Vehicular Environments)

On the need for bidirectional coupling of road traffic microsimulation and network simulation - Sommer, Christoph; Yao, Zheng; German, Reinhard; Dressler, Falko (Proceeding of the 1st ACM SIGMOBILE workshop on Mobility models - MobilityModels '08)

Progressing toward realistic mobility models in VANET simulations - Sommer, Christoph; Dressler, Falko (IEEE Communications Magazine)

Tomografische Ultraschallmessverfahren für die Prozessmesstechnik - Henning, Bernd

Editorial: XXI. Messtechnisches Symposium des Arbeitskreises der Hochschullehrer für Messtechnik (AHMT), Paderborn, 20.--22.09.2007 - Henning, Bernd (Technisches Messen)

Verfahren zur Bestimmung einer Eigenschaft eines strömenden Mediums sowie Ultraschallzähler - Henning, Bernd

Separation und Bewertung verschiedener Moden der Schallausbreitung im akustischen Wellenleiter - Rautenberg, Jens; Henning, Bernd
In this contribution it is shown that the modal components of the received signal at the end of an acoustic waveguide can be suppressed or intensified if the two electrodes of a piezo-electric ceramic are shaped in a special way. With this it is possible to measure different signals which can be used to differ between the liquids dissipation and the signal attenuation caused by the waveguide geometry as well as impedance conditions. With the help of the principal component analysis it should be possible to infer the modal amplitudes from the received signals of one ultrasonic transducer and to calculate the acoustic impedance of the liquid that is included in the wave guide.

Simultaneous direct and indirect measurement of sound velocities - Rautenberg, Jens; Henning, Bernd
This contribution is about different types of sonagram processing and their application for the simultaneous direct and indirect measurement of both the longitudinal and the transversal ultrasound velocities of highly absorbing isotropic synthetic polymers. Therefore, the pulse transmission of an initially longitudinal wave through a hollow cylindrical specimen is investigated experimentally and theoretically.

Piezosensor zur Temperaturmessung - Rautenberg, Jens; Ziegler, Horst; Gaugler, Ulrich; Dietz, Gerhard; Unverzagt, Carsten; Kehl, Romina; Henning, Bernd

Verfahren zur Bestimmung einer Eigenschaft eines strömenden Mediums - Rautenberg, Jens; Ziegler, Horst; Gaugler, Ulrich; Dietz, Gerhard; Unverzagt, Carsten; Kehl, Romina; Henning, Bernd

Block Model: an educational model of program comprehension as a tool for a scholarly approach to teaching - Schulte, Carsten (ICER)

Duality Reconstruction - Teaching Digital Artifacts from a Socio-technical Perspective - Schulte, Carsten (ISSEP)

What are information technology's key qualifications? - Dörge, Christina; Schulte, Carsten (ITiCSE)

Digitale Artefakte und Schlüsselkompetenzen im Informatikunterricht der Sekundarstufe I - Schulte, Carsten; Dörge, Christina (DDI)

Weighted voting as approximate MAP prediction in pairwise classification - Hüllermeier, Eyke; Vanderlooy, S. (In Proceedings Workshop LWA-2008, Lernen-Wissensentdeckung-Adaptivität, Würzburg, Germany)

Evolutionary construction of multiple graph alignments for mining structured biomolecular data - Fober, T.; Hüllermeier, Eyke; Mernberger, M. (In Proceedings Workshop LWA-2008, Lernen-Wissensentdeckung-Adaptivität, Würzburg, Germany)

Evolutionary construction of multiple graph alignments for the structural analysis of biomolecules - Fober, T.; Hüllermeier, Eyke; Mernberger, M. (iIn Proceedings GCB-2008, Germany Conference on Bioinformatics, Dresden 2008)

Internationalisierung, Unternehmensgröße und Konzernsteuerquote - Bischoff, Dennis; Halberstadt, Alexander; Sureth, Caren

Income-Related Minimum Taxation Concepts and Their Impact on Corporate Investment Decisions - Dahle, Claudia; Sureth-Sloane, Caren

arqus-Stellungnahme zur notwendigen Reform der Abgeltungssteuer - Kiesewetter, Dirk; Niemann, Rainer; Hundsdoerfer, Jochen; Knirsch, Deborah; König, Rolf; Kruschwitz, Lutz; Löffler, Andreas; Maiterth, Ralf; Müller, Heiko; Sureth-Sloane, Caren; Treisch, Corinna (Der Betrieb)

arqus-Stellungnahme: Das BilMoG - Eine Chance zur Steuervereinfachung? - Knirsch, Deborah; Müller, Heiko; Blaufus, Kay; Hundsdoerfer, Jochen; Kiesewetter, Dirk; König, Rolf; Kruschwitz, Lutz; Löffler, Andreas; Maiterth, Ralf; Müller, Heiko; Sureth-Sloane, Caren; Treisch, Corinna (Deutsches Steuerrecht)

The Impact of Thin Captialization Rules on Shareholder Financing - Maßbaum, Alexandra; Sureth-Sloane, Caren

Unternehmensbewertung für substanzsteuerliche Zwecke - Eine empirische Analyser des Stuttgarter Verfahrens und alternative Ansätze - Müller, Jens; Sureth-Sloane, Caren

Steuern und Risiko als substitutionale oder komplementäre Determinanten unternehmerischer Investitionspolitik? - Niemann, Rainer; Sureth-Sloane, Caren

Auswirkungen einer Reform des Erbschaft- und Schenkungsteuergesetzes auf das Steueraufkommen unter besonderer Berücksichtigung einer verkehrswertorientierten Bewertung von Unternehmens- und Grundvermögen - Sureth-Sloane, Caren; Müller, Jens; Houben, Henriette; Maiterth, Ralf (Untrnehmensbesteuerung 2008: Neue Wege gehen)

Kritische Anmerkungen zur Ermittlung des tatsächlichen Werts einer Familienpersonengesellschaft nach neuer Rechtslage - Sureth-Sloane, Caren; Nordhoff, Daniel (Der Betrieb)

Praxisnähe und universitäre Ausbildung: Fallstudie der Universität Paderborn - Sureth-Sloane, Caren; Nordhoff, Daniel (DATEV BILDUNGSforum)

Proposals for a European Corporate Taxation and Their Influence on Multinationals' Tax Planning - Sureth-Sloane, Caren; Üffing, Michaela

Neural networks in 3D medical scan visualization - Zukic, D.; Elsner, A.; Avdagic, Z.; Domik, Gitta (Proceedings of 11th International Conference on Computer Graphics and Artificial Intelligence)

Navigierbare Kompression von XML-Datenströmen - Hartel, Rita

Detecting Suspicious Relational Database Queries - Böttcher, Stefan; Hartel, Rita; Kirschner, Matthias (Third International Conference on Availability, Reliability and Security)

BSBC: Towards a Succinct Data Format for XML Streams - Böttcher, Stefan; Hartel, Rita; Heinzemann, Christian (WEBIST 2008, Proceedings of the Fourth International Conference on Web Information Systems and Technologies)

Compressing XML Data Streams with DAG+BSBC - Böttcher, Stefan; Hartel, Rita; Heinzemann, Christian (Web Information Systems and Technologies, 4th International Conference, WEBIST 2008, Revised Selected Papers)

Ultraschall-Messtechnik und Ultraschall-Tomografie - Henning, Bernd

Development status and market potential of hot formed ballistic steels - Tröster, Thomas; Howe, C.; Müller, M.; Rostek, W.

The Effect of Texture on the Fatigue Properties of Ultrafine-Grained Interstitial-Free Steel - Niendorf, Thomas; Marten, Thorsten; Maier, Hans J.; Karaman, Ibrahim (Materials Science Forum)
The present paper reports on the effect of texture on the cyclic stress-strain response (CSSR) and the fatigue life of ultrafine-grained (UFG) interstitial-free (IF) steel. Tests in the lowcycle fatigue (LCF) regime were conducted on material that was processed by the equal channel angular extrusion (ECAE) technique along the so called “efficient” route 8E. This route has been shown to result in a homogeneous microstructure with a high fraction of high angle grain boundaries (HAGBs), which are beneficial for a stable CSSR. In addition, the evolution of the microstructure was characterized by means of electron optical techniques, including electron backscattered diffraction, and by X-Ray diffractometry. It was found that the initial texture of specimens cut from the ECAE billet along different orientations with respect to the extrusion direction (ED) has a substantial effect on the CSSR of the UFG IF steel. Furthermore, microscopy results indicated the notable influence of the last ECAE processing step on the evolution of damage in the material.

Is an ordinal class structure useful in classifier learning? - Hühn, J.; Hüllermeier, Eyke (International Journal of Data Mining, Modeling and Management)

Label ranking by learning pairwise preferences - Hüllermeier, Eyke; Fürnkranz, J.; Cheng, W.; Brinker, K. (Artificial Intelligence)

A critical analysis of variants of the AUC - Vanderlooy, S.; Hüllermeier, Eyke (Machine Learning)

Multilabel classification via calibrated label ranking - Fürnkranz, J.; Hüllermeier, Eyke; Mencia, E.; Brinker, K. (Machine Learning)

Learning valued preference structures for solving classification problems - Hüllermeier, Eyke; Brinker, K. (Fuzzy Sets and Systems)

Case-based learning in a bipolar possibilistic framework - Beringer, J.; Hüllermeier, Eyke (International Journal of Intelligent Systems)

Granular computing in machine learning and data mining - Hüllermeier, Eyke (Handbook on Granular Computing)

Ein verfeinertes elektrisches Modell für Teilchentreffer und dessen Auswirkung auf die Bewertung der Schaltungsempfindlichkeit - Coym, Torsten; Hellebrand, Sybille; Ludwig, Stefan; Straube, Bernd; Wunderlich, Hans-Joachim; G. Zoellin, Christian
Keywords: WORKSHOP

Testen mit Rücksetzpunkten - ein Ansatz zur Verbesserung der Ausbeute bei robusten Schaltungen - Amgalan, Uranmandakh; Hachmann, Christian; Hellebrand, Sybille; Wunderlich, Hans-Joachim
Keywords: WORKSHOP

Research Note: Towards Dynamic Visualization for Understanding Evolution of Digital Communication Networks - Trier, Matthias (Information Systems Research)

Research Note—Towards Dynamic Visualization for Understanding Evolution of Digital Communication Networks - Trier, Matthias (Information Systems Research)

Multimedia Production with a Content HUB Environment. Media Engineering for Mobile Computing Courseware - Herzog, Michael A.; Trier, Matthias (2007 4th IEEE Workshop on Intelligent Data Acquisition and Advanced Computing Systems: Technology and Applications)

SCORM (Shared Content Object Reference Model) - Trier, Matthias (Enzyklopädie der Wirtschaftsinformatik – Online-Lexikon)

Workflow-Modellierung - Krallmann, H.; Trier, Matthias (Enzyklopädie der Wirtschaftsinformatik – Online-Lexikon)

Systemanalyse - Krallmann, H.; Trier, Matthias (Enzyklopädie der Wirtschaftsinformatik – Online-Lexikon)